New Blood Level Measurement System in Blood Separating Machine - Miloš Petković; Miroslav Božić; Dragiša Popović; Darko Todorović; Goran S. Đorđević (Electronics, 2014)
Standard versions of blood separators typically use medium-price color sensors for a detection of a boundary level between red blood cells and plasma, at the last gate – at hose clamps. Discrete number of sensors is related to a number of significant levels to be detected thus making blood separation potentially faulty and unreliable. Our target was to make flexible, low cost replacement for level detection system that can be easily integrated into the existing product. We came up with an image processing solution that uses USB web-camera, ARM based off-the-shelf board – BeagleBone black and free OpenCV library. Flexibility is held in much higher, selectable number of levels, freely positioned USB camera and brand-free independent processing platform, as well as semi-automatic calibration system. By adding minimum additional electronics, we managed to integrate our solution into existing Blood processing machine. In conclusion, we added a new value to the machine at lower cost in production, increasing measurement frequency and resolution needed for improvement of blood separation process. Next step is to try to use two USB cameras on a custom-made board, for simultaneous level detection on two-channel blood separator, bringing the system integration to the higher level.